Changes in muscle damage, inflammation, and fatigue-related parameters in young elite soccer players after a match - Romagnoli, M.; Sanchis-Gomar, F.; Alis, R.; Risso-Ballester, J.; Bosio, A.; Graziani, R. L.; Rampinini, E. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Professional soccer players are subjected to substantial physical loads during competitive seasons. We aimed to explore the changes induced by a soccer match on muscle damage and inflammation biomarkers, and their relationship with fatigue parameters.